2018
DOI: 10.1111/are.13883
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fish oil with difference oxidation degree on growth performance and expression abundance of antioxidant and fat metabolism genes in orange spotted grouper,Epinephelus coioides

Abstract: The present study was designed to assess the effects of fish oil with different oxidation degree on growth performance, serum biochemistry parameters and expressive abundance of oxidative stress and fat metabolism genes of orange spotted grouper Epinephelus coioides. The oxidized fish oil was conducted as follows: storage temperature: 4°C, ambient temperature (AT, [31.5 ± 3.5]°C); storage time: 45, 90, 135 days; antioxidant contents: 30 mg/kg (ethoxyquin [EQ]), 300 mg/kg Higher EQ (HEQ). According to the diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 60 publications
1
8
0
Order By: Relevance
“…In this study, oxidized-fish-oil diets significantly reduced the growth performance of channel catfish, which is similar to results obtained in juvenile hybrid grouper (♀ Epinephelus fuscoguttatus × ♂ Epinephelus lanceolatus ) [ 24 ], farmed tilapia [ 6 ], orange spotted grouper [ 5 ], and yellow catfish ( Pelteobagrus fulvidraco ) [ 25 ]. One of the reasons is that toxic and harmful substances such as lipid hydroperoxides, ketones, aldehydes, and acids are produced after oxidation of fish oil, which induces oxidative stress, leads to inflammatory response, and then inhibits growth [ 5 ]. Another reason is that oxidized fish oil has reduced nutritional value compared with non-oxidized fish oil [ 26 ].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…In this study, oxidized-fish-oil diets significantly reduced the growth performance of channel catfish, which is similar to results obtained in juvenile hybrid grouper (♀ Epinephelus fuscoguttatus × ♂ Epinephelus lanceolatus ) [ 24 ], farmed tilapia [ 6 ], orange spotted grouper [ 5 ], and yellow catfish ( Pelteobagrus fulvidraco ) [ 25 ]. One of the reasons is that toxic and harmful substances such as lipid hydroperoxides, ketones, aldehydes, and acids are produced after oxidation of fish oil, which induces oxidative stress, leads to inflammatory response, and then inhibits growth [ 5 ]. Another reason is that oxidized fish oil has reduced nutritional value compared with non-oxidized fish oil [ 26 ].…”
Section: Discussionsupporting
confidence: 84%
“…Compared with soybean oil, fish oil has a high content of unsaturated fatty acids (HUFAs), such as eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), and a good feeding attraction effect, so it is the best lipid source for aquatic animals [ 2 , 3 ]. However, EPA and DHA are easily oxidized during the storage and processing of fish oil and feed, producing harmful substances such as lipid hydroperoxides, ketones, aldehydes, and acids [ 4 , 5 ]. Studies have also reported that feeding an oxidized-fish-oil diet has been found to decrease growth performance and cause oxidative stress of tilapia ( Oreochromis niloticus ) [ 6 ], Wuchang bream ( Megalobrama amblycephala ) [ 7 ], and orange spotted grouper ( Epinephelus coioides ) [ 5 ], disrupt lipid metabolism of Rhynchocypris lagowski Dybowski [ 8 ], and induce intestinal injury of Megalobrama amblycephala [ 9 ] and rice field eel ( Monopterus albus ) [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This analysis uses KOBAS (http://kobas.cbi.pku.edu.cn/home.do) for KEGG pathway enrichment analysis, the relevant parameter -mf (statistic method, f is Fisher's exact test), indicating the use of Fisher's accurate test method for statistics, -n BH (false discovery rate (FDR) correction method:), indicating that the false discovery rate method is used for verification to control the calculation of the false positive rate, the corrected p value 0.05 is the threshold, and the KEGG pathway that satisfies this condition is defined as the KEGG pathway that is significantly enriched in differentially expressed proteins (*p < 0. body was maintained in a state of dynamic equilibrium to protect the body from damage (Wang et al, 2019). The activity of antioxidant enzymes is closely connected with lipid peroxidation under stress, and SOD is considered to be the vital first-line defence against oxidative stress (Liu et al, 2019;Zheng et al, 2016). The results of the present study showed that the 20 d fasting promoted the activity of SOD to protect S. barcoo from hunger stress.…”
Section: Discussionmentioning
confidence: 53%
“…Likewise, Gao et al (2012) reported the increment of plasma TG concentration in red sea bream fed OFO and increasing dietary VE level reduced its concentration. Also, feeding diets containing highly oxidized fish oil led to elevated serum TG level in orange spotted grouper (Epinephelus coioides) (Liu et al, 2019). Impacts of oil oxidation on lipid metabolism has been barely investigated in fish, however, studies on rats revealed suppressed activity of hepatic enzymes which are involved in fatty acids synthesis (Eder and Kirchgessner, 1998;Lamboni et al, 1998).…”
Section: Discussionmentioning
confidence: 99%